İBN SİNA'NIN 'DÜŞÜNEN NEFSİ VE DURUMLARINI TANIMA' ADLI RİSALENİN ÇEVİRİ VE İNCELEMESİ - Hasan Akkanat (Felsefe Dünyası)
İBN SİNA'NIN 'DÜŞÜNEN NEFSİ VE DURUMLARINI TANIMA' ADLI RİSALENİN ÇEVİRİ VE İNCELEMESİ